Association of IL-4 and IL-4R Polymorphisms with Litter Size Traits in Pigs - Worrarak Norseeda; Guisheng Liu; Tawatchai Teltathum; Pantaporn Supakankul; Korawan Sringarm; Watcharapong Naraballobh; Trisadee Khamlor; Siriwadee Chomdej; Korakot Nganvongpanit; Patcharin Krutmuang; Supamit Mekchay (Animals, 2021)
The interleukin-4 (IL-4) and interleukin-4 receptor (IL-4R) are cytokines that are involved in the immune and reproductive systems. This study aimed to verify the polymorphisms in the porcine IL-4 and IL-4R genes and to assess their effects on litter size traits in commercial pigs. Single nucleotide polymorphisms (SNPs) in the porcine IL-4 and IL-4R genes were genotyped by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. A non-coding SNP of IL-4 g.134993898T > C and a non-synonymous SNP of IL-4R c.1577A > T (amino acid change at position 526, Q526L) were found to be segregating in Landrace sows. The IL-4 g.134993898T > C polymorphism was significantly associated with the number of piglets weaned alive (NWA) trait. The IL-4R c.1577A > T polymorphism was significantly associated with the number born alive (NBA) and NWA traits. Moreover, the accumulation of favorable alleles of these two SNP markers revealed significant associations with the NBA, NWA, and mean weight of piglets at weaning (MWW) traits. These findings indicate that the porcine IL-4 and IL-4R genes may contribute to the reproductive traits of pigs and could be used as candidate genes to improve litter size traits in the pig breeding industry.